Children’s bond with companion animals and associations with psychosocial health: A systematic review - Groenewoud, Daniëlle; Enders-Slegers, Marie-Jose; Leontjevas, Roeslan; van Dijke, Annemiek; de Winkel, Tynke; Hediger, Karin (Frontiers in Psychology, 2023)
Background: Companion animals can fulfill children’s attachment needs. A secure attachment to humans is positively associated with psychosocial health, therefore, the extent to which this applies to a child-companion animal bond is worth examining. Aims: We aimed to gain insight into the current literature regarding the bond between children and companion animals and psychosocial health. We focused on (1) the correlation between the child-companion animal bond and psychosocial health; (2) characteristics of children and companion animals and the strength of their bond; (3) the correlations between parental attachment and the child-companion animal bond; and (4) the instruments used to measure the child-companion animal bond. Method: We searched three major electronic databases for studies reporting quantitative and qualitative data on child-companion animal bonds and children’s psychosocial health. Reports with participants younger than 18 years of age were included. Results: The search revealed 1025 unique records, of which we included 29 studies. Some positive associations were reported between the strength of the child-companion animal bond and children’s psychosocial health outcomes like empathy, social support, and quality of life, although some results were contradictory. The child–companion animal bond was the strongest with dogs, followed by cats and other mammals. Overall, girls reported a stronger bond with companion animals than boys. Most of the instruments currently used, measure the strength of the bond. They do not measure attachment style, but do assess attachment related features. A secure attachment style to parents was positively associated with a stronger child–companion animal bond. Discussion: This review suggests that the child-companion animal bond could be beneficial for children’s psychosocial health. However, not every relationship develops into an attachment. Bonds that only partly fulfill the attachment criteria might be seen as companionship, support, or ownership. Since a strong bond with animals might not be the same as a secure attachment, we advise to modify human attachment instruments, in order to effectively study children’s attachment to companion animals. Lastly, research designs that are able to investigate the causality of the relationship between the child-companion animal bond and psychosocial health are required.